2018
DOI: 10.12688/gatesopenres.12786.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the cost-per-QALYs gained and cost-per-DALYs averted literatures

Abstract: Background: We examined the similarities and differences between studies using two common metrics used in cost-effectiveness analyses (CEAs): cost per quality-adjusted life years (QALYs) gained and cost per disability-adjusted life year (DALY) averted. Methods: We used the Tufts Medical Center CEA Registry, which contains English-language cost-per-QALY gained studies, and  Global Cost-Effectiveness Analysis (GHCEA) Registry, which contains cost-per-DALY averted studies. We examined study characteristics includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In order to use WHO’s suggested threshold, the ICER should be in terms of cost per DALY (disability-adjusted life year) [7], however according to a study that reviewed the cost-effectiveness literature, it was found that cost-per quality adjusted life year (QALY) is used to address diseases in wealthier countries such as cancer, whereas cost-per DALY tend to address more prevalent diseases in low income countries such as HIV. Furthermore, QALYs tend to be used for interventions that evaluate pharmaceuticals, while DALYs are used to evaluate interventions that are more focused on immunizations [8]. Additionally, the use of a figure close to the GDP per capita as a cost-effectiveness threshold is widespread in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…In order to use WHO’s suggested threshold, the ICER should be in terms of cost per DALY (disability-adjusted life year) [7], however according to a study that reviewed the cost-effectiveness literature, it was found that cost-per quality adjusted life year (QALY) is used to address diseases in wealthier countries such as cancer, whereas cost-per DALY tend to address more prevalent diseases in low income countries such as HIV. Furthermore, QALYs tend to be used for interventions that evaluate pharmaceuticals, while DALYs are used to evaluate interventions that are more focused on immunizations [8]. Additionally, the use of a figure close to the GDP per capita as a cost-effectiveness threshold is widespread in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, CUA is the gold standard for economic evaluation, since it uses utility-based units as outcomes (such as cost per QALYs gained or DALYs averted), which enables the comparison of various type of interventions and disease conditions. A previous review indicated that QALYs were more popular in high income countries, while low and low-middle income countries mostly used DALYs averted [71]. A key benefit of the utility-based units CUA uses is that they consider both the patients’ quality of life/health and the effects of interventions on mortality, which are more important than purely clinical outcomes often used in CEA.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear explanation for these inconsistencies. As we have noted elsewhere, decisions to fund or conduct economic evaluations reflect not just the disease burden imposed by the targeted condition, but also the number of promising interventions or programs 19 , 20 . Because specialty drugs for diseases such as cancer represent important new interventions in high-income countries, and because pharmaceutical companies have the resources and incentive to characterize value for those interventions, much of the cost-per-QALY literature has recently focused on specialty drug therapies.…”
Section: Discussionmentioning
confidence: 99%